Pengembangan Model Laboratorium Tumbuh Kembang Anak “Audhi Day care” di UAI - Nurfadilah Nurfadilah; Nila Fitria; Rohita Rohita (Universitas Al Azhar Indonesia, 2023)
Day care is an ECD service that assists working parents in providing health, care, protection, and education for children. The PG PAUD study program plans to develop